Capacidade funcional, função renal e vitamina D em idosos com idade acima de 80 anos - projeto longevos - Araújo, Lara Miguel Quirino [UNIFESP] (2016)
Background: Identifying biomarkers associated with a good functional capacity can contribute to preventive and therapeutic measures. The decline in renal function and vitamin D deficiency are common in the elderly and FGF23 is associated with aging in an animal model. The aim of this study was to examine the relationship between functional capacity and renal function (by estimated glomerular filtration rate), vitamin D (25(OH)D) and FGF23 in the elderly aged 80 years and older. Methods: We evaluated 205 community-dwelling elderly independent for self-care. The performance of Instrumental Activities of Daily Living (IADL), Mini-Mental State Examination (MMSE), verbal fluency test, handgrip and time to sit and rising from a chair five times was analysed. We measured creatinine, cystatin C, 25(OH)D levels and cFGF23. The GFR was estimated by CKD-EPI equation based on creatinine and cystatin C. Results: In 205 oldest old, the mean eGFR was 51 ± 14 ml/min/1.73m2 and the mean 25(OH)D was 19.8 (± 8.1) ng/mL. The mean age of participants was 85 years, 68% were female, 66.7% were Caucasian, with mean number of 4 chronic conditions associated and were taking a mean number of 6 medications. The first tertile of eGFR (range 17-45 ml/min/1.73m2) was associated with age (p = 0.001) and a worse performance in IADL (p = 0.038), and was not associated with general health measures or cognitive performance. Individuals in the lowest 25(OH)D tertile (ranging from 5.8 to 15 ng/ml) were older (p= 0.037), was taking less vitamin D supplements (p <0.001) and had less chronic diseases (p= 0.041) and higher impaired functional capacity (AIVD, p <0.001; VF, p= 0.022 and grip strength, p= 0.008). These associations remained non-significant in the multivariate analysis, but BMI was associated with VF and IADL (p = 0.037 and 0.024, respectively). In 144 volunteers, we measured cFGF23 and it was not associated with functional performance. To each increase of 1mg / mL in cystatin C, there was an increase of 83.71 RU / mL in cFGF23. There was no association between cFGF23 with 25(OH)D.The cFGF23 first tertil group (<54.4 RU / mL) had the highest eGFR (58 ± 12 ml/min/m2, p <0.001), the highest level of hemoglobin (13.9 ± 1.2 g / dL), had less chronic conditions (3.9 ± 1.9; p = 0.018) and were taking the lowest number of medications (4.9 ± 2.1, p = 0.008). The higher cFGF23 tertile group (? 92.6 U / mL) had the higher mean age. Conclusion: The lower eGFR was associated with worse performance in IADL. Individuals in the lowest 25(OH)D tertile had more impaired functional capacity. There was no significant interaction between eGFR and 25(OH)D associated with functional capacity tests. The group with the lowest cFGF23 (<54.4 RU/mL) had better kidney function, higher hemoglobin level, less chronic conditions and were taking less medications.